2020
DOI: 10.1111/mec.15773
|View full text |Cite
|
Sign up to set email alerts
|

Winter warming rapidly increases carbon degradation capacities of fungal communities in tundra soil: Potential consequences on carbon stability

Abstract: High‐latitude tundra ecosystems are increasingly affected by climate warming. As an important fraction of soil microorganisms, fungi play essential roles in carbon degradation, especially the old, chemically recalcitrant carbon. However, it remains obscure how fungi respond to climate warming and whether fungi, in turn, affect carbon stability of tundra. In a 2‐year winter soil warming experiment of 2°C by snow fences, we investigated responses of fungal communities to warming in the active layer of an Alaskan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 60 publications
0
9
0
Order By: Relevance
“…Most root N uptake activities are ceased in winter or at a much lower rate than during the growing season (Comerford et al, 2013; Larsen et al, 2012; Ma et al, 2021; Sanders‐DeMott et al, 2018). However, fungi often reach their peak biomass during wintertime, and the activities of de‐polymerase enzymes can maintain a high rate under snowpack (Cheng et al, 2021; Kaiser et al, 2011; Kuhnert et al, 2012; Schmidt et al, 2007). In addition, because of the inherent high N uptake capacity of microbes (i.e., the high surface‐area‐to‐volume ratios) (Kuzyakov & Xu, 2013), the bioavailable N released during organic matter decomposition could be efficiently immobilized by microorganisms (Grogan & Jonasson, 2003; Jaeger et al, 1999; Schmidt et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Most root N uptake activities are ceased in winter or at a much lower rate than during the growing season (Comerford et al, 2013; Larsen et al, 2012; Ma et al, 2021; Sanders‐DeMott et al, 2018). However, fungi often reach their peak biomass during wintertime, and the activities of de‐polymerase enzymes can maintain a high rate under snowpack (Cheng et al, 2021; Kaiser et al, 2011; Kuhnert et al, 2012; Schmidt et al, 2007). In addition, because of the inherent high N uptake capacity of microbes (i.e., the high surface‐area‐to‐volume ratios) (Kuzyakov & Xu, 2013), the bioavailable N released during organic matter decomposition could be efficiently immobilized by microorganisms (Grogan & Jonasson, 2003; Jaeger et al, 1999; Schmidt et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…However, less attention has been paid to microbial interactions under warming, despite the fact that soil microbes are linked by strong ecological interactions and shifts in those microbial interactions might affect ecosystem functioning (de Vries et al, 2013; Faust & Raes, 2012). Only interactions within certain microbial communities, such as prokaryotes and fungi under warming were explored in previous network analyses (Cheng et al, 2021; Deng et al, 2012; Yuan et al, 2021). Different microbial groups displayed varied resistance to warming (Treseder et al, 2016), but whether these differences would further influence cross‐trophic interactions had not been adequately investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, molecular ecological network analyses (MENA) show robustness against data noise and could link network topological properties with environmental factors (Deng et al, 2012). Some studies based on MENA have shown that warming modified the interaction patterns within bacterial and fungal communities (Cheng et al, 2021; Yuan et al, 2021). Yuan et al (2021) confirmed that warming gradually enhanced microbial network (bacterial and archaea) complexity and stability in a semiarid grassland.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have suggested that shifts of microbial community composition responding to altitude were often dependent on temperature variations (Frindte et al, 2019;Ren et al, 2021). For instance, decreased temperature along increasing altitude would favor the dominance of fungal communities that preferentially utilize recalcitrant C, as lower temperature was more optimal for fungal growth compared with bacteria (Cheng et al, 2021;Whitaker et al, 2014). According to the C quality temperature hypothesis, the decomposition of low-quality substrate (recalcitrant C) is more sensitive to temperature changes than the high-quality substrate (labile C) because of its higher activation energy (Lefevre et al, 2014;Wang et al, 2018).…”
Section: Discussionmentioning
confidence: 99%